MutS regulates access of the error-prone DNA polymerase Pol IV to replication sites: a novel mechanism for maintaining replication fidelity - Margara, Lucía (2016)
Translesion DNA polymerases (Pol) function in the bypass of template lesions to relieve stalled replication forks but also display potentially deleterious mutagenic phenotypes that contribute to antibiotic resistance in bacteria and lead to human disease. Effective activity of these enzymes requires association with ring-shaped processivity factors, which dictate their access to sites of DNA synthesis. Here, we show for the first time that the mismatch repair protein MutS plays a role in regulating access of the conserved Y-family Pol IV to replication sites. Our biochemical data reveals that MutS inhibits the interaction of Pol IV with the β clamp processivity factor by competing for binding to the ring. Moreover, the MutS–β clamp association is critical for controlling Pol IV mutagenic replication under normal growth conditions. Thus, our findings reveal important insights into a non-canonical function of MutS in the regulation of a replication activity.